Digitalisasi Prosedur Pajak melalui Coretax: Studi Kualitatif tentang Tantangan dan Peluang bagi Pengguna di Sektor Pariwisata Bandung - Zhafira Citra Paramita; Vivin Alifianti Rusyana; Harmon Chaniago (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The rapid development of digital technology in recent years has driven the transformation of tax administration systems in Indonesia. Aligning with global trends, the government, through the Directorate General of Taxes, launched Coretax (Compliance and Risk Management System for Taxation) as part of a digital-based tax modernization strategy. This qualitative study explores the challenges and opportunities of Coretax adoption among tourism sector users in Bandung. Data were collected through in-depth interviews with key informants from tourism businesses and analyzed using thematic and SWOT analysis. The findings reveal that while Coretax offers benefits such as system integration, faster reporting, and reduced input errors, its implementation faces significant obstacles, including system instability, limited IT support, and low digital literacy. The study concludes with recommendations to enhance system stability, improve technical support, and strengthen digital literacy to optimize Coretax adoption.